Association between antispasmodics and detection of lesions by screening esophagogastroduodenoscopy. Issue 11 (20th October 2022) - Iwagami, Hiroyoshi; Seta, Takeshi; Nakano, Shogo; Wakita, Midori; Konishi, Takafumi; Matsumoto, Hisakazu; Nakatani, Yasuki; Akamatsu, Takuji; Urai, Shunji; Uenoyama, Yoshito; Yamashita, Yukitaka; Nakayama, Takeo
Abstract: Background and Aim: Whether administration of antispasmodics as a component of premedication contributes to detection of lesions by screening esophagogastroduodenoscopy (EGDS) remains unclear. Our primary aim was to investigate this possibility. Methods: The cohort in this retrospective study comprised consecutive asymptomatic individuals who had undergone screening EGDS as part of a health check‐up at the Japanese Red Cross Wakayama Medical Center from October 2015 to September 2020. The investigated lesions comprised esophageal squamous cell carcinoma or adenocarcinoma, gastric adenoma or adenocarcinoma, and duodenal adenoma or adenocarcinoma. Results: Targeted lesions were detected in 72 of 31 484 participants (0.23%), 18 260 and 13 224 of whom had received and not received pre‐procedure antispasmodics, respectively. The rates of detection of lesions in these groups were 0.21% (38/18260) and 0.26% (34/13224), respectively ( P = 0.40). Multivariate logistic regression analysis showed no association between administration of antispasmodics and rates of detection of targeted lesions [ P = 0.24, Odds ratio (95% CI): 1.46 (0.78–2.75)]. Conclusions: Antispasmodics, which were administered to more than half of the study cohort, did not improve the rate of detection of targeted lesions. Abstract : We investigated whether administration of antispasmodics as a component of premedication contributes to detection of lesions by screening esophagogastroduodenoscopy. Antispasmodics, which were administered to more than half of the study cohort, did not improve the rate of detection of targeted lesions.